Secukinumab Therapy in Psoriasis Management - Ira Yunita; Sylvia Anggraeni (Berkala Ilmu Kesehatan Kulit dan Kelamin, 2022)
Background : In recent years, use of biological therapy in psoriasis has increased as a result of advances in understanding the pathophysiology of psoriasis disease. Biological agents currently approved for the treatment of moderate to severe plaque psoriasis including inhibitor TNF-α (adalimumab, etanercept, infliximab), inhibitor IL-17 (ixekizumab, brodalumab, secukinumab), inhibitor IL-12/IL-23 (ustekinumab), and inhibitor IL-23 (guselkumab, tildrakizumab). Secukinumab is a human monoclonal antibody that selectively neutralizes IL-17A, a cytokine involved in the development of psoriasis. Review: Psoriasis is a chronic skin inflammation with the characteristic form of erythematous plaque firmly, thick scale, layered, and silvery-white. The trigger factors cause damage to the skin and produce cytokines IFN-γ, TNF-α, IL-17, and IL-22. This proinflammatory cytokine induces the proliferation of keratinocytes and subsequently causes skin inflammation, leading to plaque psoriasis formation. Biologic agents are utilized to block those cytokines. There are three main classes of biological agents in the treatment of psoriasis: inhibitor TNFα, inhibitor IL-17, and inhibitor IL-23. Secukinumab is a fully human antibody that selectively binds and neutralizes IL-17A. Conclusion: Biological agents targeting IL-17 receptors are more effective and safer than biological agents that target TNF-α and IL-23 receptors for moderate to severe plaque psoriasis treatment. Secukinumab has been approved for plaque psoriasis therapy in adults, psoriasis arthritis (PsA), and ankylosing spondylitis.